Satisfaction of Student Academic Services: Survey on Students of IAIN Syaikh Abdurrahman Siddik Bangka Belitung - Dinar Pratama (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
An efforts to improve the quality in higher education needs to be done on an ongoing basis. One way is by providing optimum academic services for students. This study aimed to describe how big the satisfaction index of students to academic services which include aspects, tangibles, reliability, empathy, responsivenes, assurance, and information systems. This study used a qualitative approach with a descriptive survey method. The population in this study were all students of IAIN SAS Bangka Belitung. Engineering samples using proportionate stratified random sampling technique. By using Taro Yamane formula obtained the number of samples are 831 students consisting of 416 students from the Department of Tarbiyah, 291 students of Syariah, and Ekonomi Islam, 125 students from the Department of Dakwah and Komunikasi. Data analysis using techniques percentage calculations and compares the percentage index consisting of a category of very satisfied, satisfied, fairly satisfied, and very dissatisfied. Results showed that the satisfaction of students to academic services at IAIN SAS Bangka Belitung consisting of aspects, tangibles, reliability, empathy, responsivenes, assurance, and information systems is still relatively low with satisfaction index of less than 60 percent, or only 43.8 percent. Abstrak Upaya untuk meningkatkan mutu di perguruan tinggi perlu dilakukan secara berkesinambungan. Salah satunya adalah dengan menyediakan pelayanan akademik yang optimal bagi mahasiswa. Penelitian ini bertujuan untuk mendeskripsikan seberapa besar indeks kepuasan mahasiswa terhadap pelayanan akademik yang meliputi aspek, tangibles, reliability, emphaty, responsivenes, assurance, dan sistem informasi. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode survey. Populasi dalam penelitian ini adalah seluruh mahasiswa IAIN SAS Bangka Belitung berjumlah 2500 mahasiswa. Teknik sampel menggunakan teknik proportionate stratified random sampling. Dengan menggunakan rumus Taro Yamane didapat jumlah sampel penelitian sebanyak 831 mahasiswa yang terdiri dari 416 mahasiswa Jurusan Tarbiyah, 291 mahasiswa Jurusan Syariah dan Ekonomi Islam, dan 125 mahasiswa Jurusan Dakwah dan Komunikasi. Analisis data menggunakan teknik perhitungan persentase lalu membandingkannya dengan indeks persentase yang terdiri dari kategori sangat puas, puas, cukup puas, dan sangat tidak puas. Hasil Penelitian menunjukkan bahwa kepuasan mahasiswa terhadap pelayanan akademik di IAIN SAS Bangka Belitung yang terdiri dari aspek, tangibles, reliability, emphaty, responsivenes, assurance, dan sistem informasi masih tergolong rendah dengan indeks kepuasan kurang dari 60 persen atau hanya 43.8 persen. Angka ini menunjukkan mahasiswa merasa cukup puas dengan pelayanan akademik yang diberikan oleh IAIN SAS Bangka Belitung.